Analysis of Students’ Reading Skill in English for the ICT Module: A Case Study of Informatics Students at Madura University - Fujiono, Fujiono (The Ellite of Unira, 2024)
This research is a case study that describes the analysis of students' reading ability in English for the ICT module. Based on the results of interviews and surveys of research locations, many students felt difficulties when reading English for the ICT module, even they do not understand the contents of the reading. Several things related to their English reading skills such as the ability to pronounce the words (Pronunciation), the ability to obtain information (Detail Information), and the ability to answer ICT questions, there are several steps taken by researchers, namely selecting English for the ICT module, compiling English for ICT questions, implementing English for ICT questions, assessing and evaluating the answers. This study was conducted to determine the level of students' reading ability in English for the ICT module which is oriented towards global world of work competition so that the researcher or teacher can provide solutions to improve the students’ English skill, especially in the field of their English reading ability. After the researcher implemented some strategies to improve the students’ reading comprehension in English for the ICT module, the researcher has found the improvement of students’ pronunciation when reading aloud, ability to obtain detail information, and the ability to answer ICT questions. On the other hand, the students felt interested, enthusiastic, and enjoyable to read English for the ICT module.